ÇOCUKLARIN GÜNLÜK YAŞAM ETKİNLİKLERİ: İSTANBUL İLİ ÖRN. - EKİCİ, Behice; ARSLAN, Günay; DONYAĞI, Nurgül Derya; ŞAHİN, Selin (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2017)
Today's children spend more time engaging in activities that do not require effort. This has an adverse effect on children's growth and development. The present study was conducted with children of the ages 5-12 enrolled at a primary school in the district of Maltepe, Istanbul Province, for the purpose of determining the scope of the children's activities of daily living. A total of 452 children volunteered for this descriptive and correlational research. The researchers collected the data with a questionnaire that they developed based on the knowledge in the literature and the advice of an expert. The data were analyzed with numbers, percentages, mean, standard deviation and the chi-squared test. It was found that 77.9% of the children played games indoors. Of the children, 68.5% watched television for >0 - <3 hours, while 73% played electronic games for 1 - 3 hours a day. It was observed that 91.8% of the children infrequently played at least one traditional game. The boys played more electronic games and engaged in sports more than the girls. In conclusion, it was revealed in the study that while children's activities of daily living should be composed of sports, games and entertaining activities according to their preferences, the children spent a great majority of their time every day playing electronic games and watching television indoors and otherwise mostly playing football, allotting lesser time to traditional games.